Development of nonlinear energy-based method (NEM) controller for 3 DOF helicopter - Pharmayeni (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Three degree-of-freedom (3 DOF) helicopter model presents a quite interesting control challenge due to its nonlinearities. It is therefore intuitive to design a controller using nonlinear techniques to control the aircraft. In this study, a Nonlinear Energybased Method (NEM) controller is designed for a 3 DOF helicopter. NEM is a nonlinear control technique used to design a controller where nonlinearities in the system are utilized to improve performance robustness and avoid excessive control of the system. It is a control design technique that exploits the energy state of a system to achieve stabilization and/or tracking. The advantages of using NEM to control systems are: it is easy to derive the equations of motion, it can handle nonlinearities in dynamical systems, modeling and controlling done in terms of energy quantities and each subsystem can be characterized by its own energy, so the analysis becomes simpler. There are four stages to design NEM controller for the 3 DOF helicopter. The stages involved are: energy-based modeling of helicopter dynamics using Euler- Lagrange formalism. Secondly, the design of the NEM controller based on passivity principle and Lyapunov stability idea is conducted in MATLAB using the nonlinear model of the helicopter. The third stage is evaluating the performance of the designed controller. This stage involves the tuning of the controller gain(s) to satisfy the design criteria. Lastly, the stage involves with robustness analysis in which the performance of the controller is tested with the presence of disturbances. The root mean square error of elevation response is 0.6013 degree and the maximum absolute error is 0.7369 degree. For pitch response the root mean square error and the maximum absolute error are zero(0). This implies that NEM can successfully control the 3 DOF helicopter even with the presence of disturbance.